Advances in Smart Vehicular Technology, Transportation, Communication and Applications Proceedings of the First International Conference on Smart Vehicular Technology, Transportation, Communication and Applications, November 6-8, 2017, Kaohsiung, Taiwan - Pan, Jeng-Shyang.; Wu, Tsu-Yang.; Zhao, Yong.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents papers from the First International Conference on Smart Vehicular Technology, Transportation, Communication and Applications (VTCA 2017). Held from 6 to 8 November 2017 in Kaohsiung, Taiwan, the conference was co-sponsored by Springer, Fujian University of Technology in China, Fujian Provincial Key Laboratory of Digital Equipment, Fujian Provincial Key Lab of Big Data Mining and Applications, and National Kaohsiung University of Applied Sciences in Taiwan. The book is a valuable resource for researchers and professionals engaged in all areas of smart vehicular technology, vehicular transportation, vehicular communication, and applications.
Easy i-Move: Structured Image Recognition Solution for Auto Guided Vehicles -- Evaluating Multi-dimensional Abilities of Bus Drivers -- Research on Detection Algorithm of Roadway Intersection Rule Detection Based on Big Data -- Predicting the Travel Time in Using Recurrent Neural Networks: A Case Study of Fuzhou -- Driving Behavior Motivation Model Research Based on Vehicle Trajectory Data -- A Ranging Algorithm for Mobile Vehicles Based on Kalman Filter -- The Evaluation of the Video Codec Performances on the Driving Recorder with Different Vehicle Speeds -- Railway Train Working Diagram Plan System -- Railway Passenger Service Mode on "Internet +" -- Design of High Speed Train Operation Plan Simulation System -- Service Quality Evaluation of Railway Freight Transportation Network Based on Bayes Theory -- Train Headway Calculation and Simulation System for High-speed Railway -- Train Scheduling for Heavy Haul Railway -- Research on Train Delay Diagnosis in Train Diagram Based on Big Data Technology -- On Linear Precoding of Unitary Space-Time Modulation for Spatial-Temporal Correlated Flat Fading Channel -- The Integration of DFX Principles with TRIZ for Product Design - A Case Study of Electric Scooter -- Adaptive Nonsmooth Attitude Tracking Control of Quadrotor UAV with Dynamic Uncertainties -- A Constructive Problem-based Course Design for Internet of Things.
Keywords: Transportation engineering; Traffic engineering; Computational intelligence; Artificial intelligence; Transportation Technology and Traffic Engineering; Computational Intelligence; Artificial Intelligence